Pros and cons of HaloPlex enrichment in cancer predisposition genetic diagnosis - Collet, Agnès; Tarabeux, Julien; Girard, Elodie; D’Enghien, Catherine Dubois; Golmard, Lisa; Deshaies, Vivien; Lermine, Alban; Laugé, Anthony; Moncoutier, Virginie; Lefol, Cédrick; Copigny, Florence; Dehainault, Catherine; Tenreiro, Henrique; Guy, Christophe; Abidallah, Khadija; Barbaroux, Catherine; Rouleau, Etienne; Servant, Nicolas; Pauw, Antoine De; Stoppa-Lyonnet, Dominique; Houdayer, Claude (AIMS Genetics, 2015)
Panel sequencing is a practical option in genetic diagnosis. Enrichment and library preparation steps are critical in the diagnostic setting. In order to test the value of HaloPlex technology in diagnosis, we designed a custom oncogenetic panel including 62 genes. The procedure was tested on a training set of 71 controls and then blindly validated on 48 consecutive hereditary breast/ovarian cancer (HBOC) patients tested negative for BRCA1/2 mutation. Libraries were sequenced on HiSeq2500 and data were analysed with our academic bioinformatics pipeline. Point mutations were detected using Varscan2, median size indels were detected using Pindel and large genomic rearrangements (LGR) were detected by DESeq. Proper coverage was obtained. However, highly variable read depth was observed within genes. Excluding pseudogene analysis, all point mutations were detected on the training set. All indels were also detected using Pindel. On the other hand, DESeq allowed LGR detection but with poor specificity, preventing its use in diagnostics. Mutations were detected in 8% of BRCA1/2-negative HBOC cases. HaloPlex technology appears to be an efficient and promising solution for gene panel diagnostics. Data analysis remains a major challenge and geneticists should enhance their bioinformatics knowledge in order to ensure good quality diagnostic results.
Keywords: HaloPlex; cancer; predisposition; genetic diagnosis; next generation sequencing; gene panel